109. Photosensitive epilepsy: Role of corpus callosum in cortical excitability. Issue 1 (January 2015) - Sartucci, F.; Bocci, T.; Torzini, A.; Caleo, M.; Giorli, E.; Restani, L.; Rossi, S.; Maffei, L.
<x xml:space="preserve">Abstract</x> Photosensitive epilepsy (PE) is a form of epileptic seizure induced by several powerful visual stimuli. Cortical mechanisms underlying paroxysmal activity have been widely studied in several ways. Here, we employed rTMS in an attempt to disclose the role of callosal input in modulating cortical visual excitability in both healthy subjects and PE patients. We enrolled 10 healthy subjects (5 males and 5 females; mean age 16.8 ± 3.4 yrs) and 5 patients (15.9 ± 4.2 yrs). Visual evoked potentials (VEPs) triggered by grating stimuli of different contrasts were recorded before and after functional inactivation of the occipital cortex of one hemisphere via off-line low-frequency repetitive transcranial magnetic stimulation (rTMS; 0.5 Hz stimulation for 20 min). VEPs were recorded in V1 before (T0), immediately after (T1) and 45′ following the end of rTMS (T2). We found that low-frequency rTMS had an inhibitory effect on VEP amplitudes at all contrasts in the treated side in controls and patients. Reduction of VEP amplitudes in the inhibited hemisphere at T1 was accompanied by an increase in VEP amplitudes in the contralateral side at mid-high contrasts (50–90%) in healthy subjects (p < 0.05). This disinhibitory effect was observed with both central and hemifield stimulation; in PE patients, we showed both a larger potentiating of VEPs amplitudes at T1 (p < 0.01) and a persistence of the disinhibitory effect at T2 (p < 0.01). No changes in VEP amplitudes were observed when rTMS was applied to a cortical site more anterior than V1. In patients with photosensitive epilepsy VEPs amplitude increases progressively when contrast rises; consequently there is no saturation of evoked responses. That could suggest an impairment of transcallosal inhibitory loops, underlying the phenomenon of contrast gain control. In fact, some forms of photosensitivity tend to improve spontaneously around 18 years age, the time at which is completed the maturation of trancallosal projections.